CHILD NURSING CARE IMPLEMENTATION OF FEEDING RULES AND FLASH CARDS AS AN EFFORT TO INCREASE MOTHER’S KNOWLEDGE OF THE NUTRITIONAL STATUS OF TODDLER: CASE REPORT - Silvia Batulingas; Meivita Dewi Purnamasari; Haryatiningsih Purwandari (International Journal of Biomedical Nursing Review, 2025)
Introduction: The golden age is a critical and important period, but this age is also prone to nutritional disorders and disease. Nutrition is one of the factors that determines success in achieving optimal growth and development. Food that is poor in quality and quantity will cause malnutrition. Therefore, it is necessary to provide feeding rules and flash cards. Purpose: Know and identify the provision of feeding rules and flash cards on the knowledge and nutritional status of children. Methods: The case study was conducted on three year old children in Grendeng, North Purwokerto, Banyumas Regency with the implementation of Evidence Based Practice (EBP) within one week. Knowledge measurement was carried out before and after implementation. Discussion: Providing feeding rules for six meetings in one week can increase the mother's knowledge. Before implementing the questionnaire results and after implementing the post test results 3/5 with indicators of nutritional. Conclusion: Providing feeding rules during six meetings within a week is effective in increasing knowledge by increasing nutritional status indicators.